Prevalence, molecular and antimicrobial resistance of Salmonella isolated from sausages in Meknes, Morocco. (April 2017) - Ed-dra, Abdelaziz; Filali, Fouzia Rhazi; Karraouan, Bouchra; El Allaoui, Abdellah; Aboulkacem, Amal; Bouchrif, Brahim
Abstract: Salmonella is among the most important food borne pathogens worldwide contaminating a wide range of animal products including meat products. The aims of this study go through two steps: The first step is to estimate the proportion of sausages products contaminated with Salmonella in Meknes city (Morocco), which were collected from various shopping sites: butchery, street vendors, supermarket and souk (Weekly market combines the population of the small villages around Meknes city). The second one is to identify serovars, to determine the antimicrobials resistance patterns of isolates and to detect the invA and spvC genes. 34 (21.79%) Salmonella were isolated, recovered 4 serogroups and 12 serotypes. The most prevalent serotypes were Salmonella Corvallis (23.53%) and Salmonella Kentucky (17.65%). All Salmonella isolates were tested for their susceptibility to 18 selected antimicrobials agents, of which 100% were resistant to at least one antimicrobial, 85.30% (29/34) were resistant to two or more antimicrobials and 44.12% (15/34) were resistant to at least three antimicrobials. All Salmonella are resistant to ampicillin, 76.47% to streptomycin, 20.59% to sulfonamides, 17.65% to Tetracycline and 11.77% to Ofloxacin. The "ACSSuT" penta-resistance pattern was observed in tow of the Salmonella Typhimurium strains. In addition, this study showed that all Salmonella strains (34) were positive for invasion gene invA and negative for the virulence gene spvC . Highlights: Salmonella was detected in 34 of the 156 samples (21.79%). 4 serogroups and 12 serotypes were identified; Salmonella Corvallis and Salmonella Kentucky were most prevalent. Multidrug resistance was found among the 15 (44.12%) Salmonella isolates. The "ACSSuT" penta-resistance pattern was observed in tow strains of the Salmonella typhimurium. The resistance to Ofloxacin was observed in 4 strains of the Salmonella Kentucky.